Validity of Erythrocyte Indices in Differentiation between Iron Deficiency Anemia and β-Thalassemia Trait in Children - Emel Uzunoğlu; Ebru Yılmaz Keskin (The Journal of Pediatric Academy, 2024)
Iron deficiency anemia (IDA) and β-thalassemia trait (BTT) are the most common causes of hypochromic microcytic anemia (HMA). Various erythrocyte indices that may help in the initial discrimination between IDA and BTT have been reported, but data evaluating their reliability in children are scarce. We aimed to evaluate the validity of 12 erythrocyte indices in the differentiation between IDA and BTT in children. These indices were red blood cell (RBC) count, Mentzer Index, England and Fraser Index, Srivastava Index, Shine and Lal Index, RBC distribution width (RDW), Ricerca Index, Green and King Index, RDW Index, Sirdah Index, Ehsani Index, and Serdar Index. Among 1,444 children with HMA, 136 (9.4%) were stratified into the IDA group and 137 (9.5%) into the BTT group. Of the 12 indices, the Green and King Index showed the highest reliability, as it had the highest Youden’s index (75.1%). Its sensitivity, specificity, positive predictive value, negative predictive value and correct diagnosis rate were 92.7%, 82.4%, 84.1%, 91.8% and 87.5%, respectively. The second most reliable index was the RDW Index, having a Youden’s index, sensitivity, specificity, positive predictive value, negative predictive value and correct diagnosis rate of 64%, 94.2%, 69.9%, 75.9%, 92.2% and 82%, respectively. Receiver operating characteristic analysis showed that the revised cut-off values for the Green and King Index and RDW Index had higher sensitivity and specificity levels than the cut-off values commonly used in the literature. The findings of this study suggest the superiority of the Green and King Index and the RDW Index as screening tools in the initial differentiation between IDA and BTT among children with HMA.